DNA-Based Taxonomy in Ecologically Versatile Microalgae: A Re-Evaluation of the Species Concept within the Coccoid Green Algal Genus Coccomyxa (Trebouxiophyceae, Chlorophyta) - Malavasi, Veronica; Škaloud, Pavel; Rindi, Fabio; Tempesta, Sabrina; Paoletti, Michela; Pasqualetti, Marcella (PloS one, 2016)
Coccomyxa is a genus of unicellular green algae of the class Trebouxiophyceae, well known for its cosmopolitan distribution and great ecological amplitude. The taxonomy of this genus has long been problematic, due to reliance on badly-defined and environmentally variable morphological characters. In this study, based on the discovery of a new species from an extreme habitat, we reassess species circumscription in Coccomyxa, a unicellular genus of the class Trebouxiophyceae, using a combination of ecological and DNA sequence data (analyzed with three different methods of algorithmic species delineation). Our results are compared with those of a recent integrative study of Darienko and colleagues that reassessed the taxonomy of Coccomyxa, recognizing 7 species in the genus. Expanding the dataset from 43 to 61 sequences (SSU + ITS rDNA) resulted in a different delimitation, supporting the recognition of a higher number of species (24 to 27 depending on the analysis used, with the 27-species scenario receiving the strongest support). Among these, C. melkonianii sp. nov. is described from material isolated from a river highly polluted by heavy metals (Rio Irvi, Sardinia, Italy). Analyses performed on ecological characters detected a significant phylogenetic signal in six different characters. We conclude that the 27-species scenario is presently the most realistic for Coccomyxa and we suggest that well-supported lineages distinguishable by ecological preferences should be recognized as different species in this genus. We also recommend that for microbial lineages in which the overall diversity is unknown and taxon sampling is sparse, as is often the case for green microalgae, the results of analyses for algorithmic DNA-based species delimitation should be interpreted with extreme caution.
Keywords: Microalgae; Sequence Analysis, DNA; Chlorophyta; Phylogeny; DNA rostlinná; sekvenční analýza DNA; DNA, Ribosomal Spacer; DNA, Plant; molekulární evoluce; Evolution, Molecular; mikrořasy; fylogeneze; mezerníky ribozomální DNA